Testosterone Replacement Therapy in Men with Prostate Cancer: What Is the Evidence?. Issue 3 (23rd September 2013) - Selph, J. Patrick; Carson, Culley C.
Abstract Introduction Testosterone is increasingly being recognized as an important hormone in maintaining proper health in aging males. Testosterone replacement therapy in older men with decreased or low‐normal testosterone levels has been recognized to improve sexual function, increase lean body mass and decrease fat mass, improve exercise‐induced coronary ischemia, and elevate mood, among other benefits. Prostate cancer remains the most common non‐skin malignancy in men in the United States, and as hypogonadism is being recognized and treated more, a dilemma has arisen: treating hypogonadism in men previously treated for prostate cancer. While testosterone replacement has traditionally been felt to be contraindicated in men with prostate cancer, recent studies have challenged this notion. Aim This review highlights the origins of this concern as well as newer data that suggest that testosterone replacement in men with prostate cancer is safe. Methods A literature search on testosterone replacement therapy in men with prostate cancer was performed. Main Outcome Measure We sought to highlight the data supporting the use of testosterone in men with prostate cancer. Results While no randomized controlled trials have been able to confirm this theory, data from multiple studies suggest that testosterone replacement is safe in selected men treated for prostate cancer. Conclusion Long‐term data and more studies are needed to conclusively change the paradigm regarding testosterone and prostate cancer growth, but based on the current data and on our experience, we feel it is safe to prescribe testosterone replacement therapy to men treated for prostate cancer with favorable pathology. Selph JP and Carson CC. Testosterone replacement therapy in men with prostate cancer: What is the evidence? Sex Med Rev 2013;1:135–142.